A Highly Efficient System for Separating Glandular and Non-glandular Trichome of Cucumber Fruit for Transcriptomic and Metabolomic Analysis - Lei Sun; Zhongxuan Feng; Fang Wang; Yu Qi; Menghang An; Lin Yang; Min Feng; Mingqi Wang; Huazhong Ren; Xingwang Liu (Bio-Protocol)
Cucumber (Cucumis sativus) trichomes play a critical role in resisting external biological and abiotic stresses. Glandular trichomes are particularly significant as they serve as sites for the synthesis and secretion of secondary metabolites, while non-glandular trichomes are pivotal for determining the appearance quality of cucumbers. However, current methods for separating trichomes encounter challenges such as low efficiency and insufficient accuracy, limiting their applicability in multi-omics sequencing studies. This protocol introduces an efficient system designed for the precise separation of glandular and non-glandular trichomes from cucumber fruit. The process begins with the pre-cooling of sorbitol buffer or ethanol solution and the RNA-free treatment of laboratory supplies, followed by sterilization and pre-cooling. After filling glass bottles with pre-cooling buffer and glass beads, cucumber ovaries are then placed in the glass bottles and the trichome is harvested by bead-beating method. The separation process involves sequential filtration through various steel sieves and centrifugation to separate trichomes. The separated trichomes obtained from this method are well-suited for subsequent multi-omics sequencing analyses. This protocol achieved high precision in separating glandular and non-glandular trichomes, significantly enhancing the efficiency of separation and sample collection processes. This advancement not only addresses existing limitations but also facilitates comprehensive studies aimed at exploring the genetic and biochemical diversity present within cucumber trichomes, thereby opening avenues for broader agricultural and biological research applications.